The Power and the Glory of Big 4: A Research Note on Independence and Competence in the Context of IFRS Implementation - Catalin Nicolae Albu; Nadia Albu; Szilveszter Fekete Pali-Pista; Dan Cuzdriorean Vladu (Journal of Accounting and Management Information Systems (JAMIS), 2011)
One of the major roles in promoting accounting convergence is played by big accounting firms (Big 4). The objective of this paper is in this context to analyze and question the role of big auditing firms in developing and implementing IFRSs worldwide, in order to better understand the convergence process. This is a research note intended to contribute to the debate on the role of auditors in general and in the context of IFRSs application in particular, to raise some questions and to identify future research directions, and to invite to reconsider the hidden aspects (both positive and negative) of apparently simple issues. We identify some questions to be addressed in the future regarding the competence of Big 4 in IFRSs, the relationship with their clients issued from this well-known competency and the associated issues of independence.
Keywords: M41; M42; G3; K2; 650; Big 4; IFRS; independence; competence